KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS FABEL TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 25 PADANG - Rahmawita, Sri; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study is three. First, describe the reading skills of fable text comprehension of class VII students of SMP Negeri 25 Padang. Second, describing fable text writing skills of class VII students of SMP Negeri 25 Padang. Third, describe the contribution of reading skills to fable text comprehension on fable text writing skills of class VII students of SMP Negeri 25 Padang. This type of research is quantitative with descriptive method. The design used in this study is design contribution. The population of this study was the seventh grade students of SMP Negeri 25 Padang who were enrolled in the 2018/2019 school year, namely as many as 250 students. The sample in this study was determined by proportional random sampling of 20% of the population, which is 48 students. The data of this study were scores on the results of reading skills tests of fable text comprehension and scores on the results of fable text writing skills. The data was obtained through two types of tests, namely objektive to measure reading skills fable text comprehension and performance tests to measure fable text writing skills. The results of this study are three. First, reading skills of fable text comprehension of class VII students of SMP Negeri 25 Padang are in good qualification (B) with an average value of 81.31. Second, fable text writing skills of grade VII students of Padang Public Middle School 25 are in good qualification (B) with an average of 77.26. Third, there is a contribution of reading skills in fable text comprehension towards fable text writing skills of class VII students of Padang State Middle School at 53.29%. Kata Kunci: Kontribusi, keterampilan membaca                    pemahaman, keterampilan menulis teks fabel